Studying neuroanatomy using MRI - Lerch, Jason P.; van der Kouwe, André J.W.; Raznahan, Armin; Paus, Tomas; Johansen-Berg, Heidi; Miller, Karla L.; Smith, Stephen M.; Fischl, Bruce; Sotiropoulos, Stamatios N. (Nature Publishing Group, 2017)
The study of neuroanatomy using imaging enables key insights into how our brains function, are shaped by genes and environment, and change with development, aging, and disease. Developments in MRI acquisition, image processing, and data modelling have been key to these advances. However, MRI provides an indirect measurement of the biological signals we aim to investigate. Thus, artifacts and key questions of correct interpretation can confound the readouts provided by anatomical MRI. In this review we provide an overview of the methods for measuring macro- and mesoscopic structure and inferring microstructural properties; we also describe key artefacts and confounds that can lead to incorrect conclusions. Ultimately, we believe that, though methods need to improve and caution is required in its interpretation, structural MRI continues to have great promise in furthering our understanding of how the brain works.